Green Logistics and Health in OBRI Economies: Does Social Marketing Matter? - Lingyun Zhang; Hsu Ling Chang; Yin Dai; Alican Umut (Frontiers Media S.A., 2022)
In this study, our primary focus is to capture the impact of green logistics and social marketing on health outcomes in One Belt Road Initiative (OBRI) countries over the time period 2007-2019. Two estimation techniques, i.e., 2SLS and GMM, are employed to get the estimates of our variables. Findings of the 2SLS model confirmed the negative impact of green logistics on infant mortality in OBRI, European, MENA, and Asian countries. On the other side, the relationship between green logistics and life expectancy is positive in all the regions in 2SLS models. The other estimation technique also supports these findings, GMM, which confirmed the negative impact of green logistics on infant mortality and the positive impact of green logistics on life expectancy OBRI, European, MENA, and Asian economies. From these findings, we can conclude that green logistics helps to improve the health status of OBRI economies. Similarly, social marketing also improves the health status in OBRI and other regions in both models. Therefore, the governments and policymakers in respective economies should focus on the development of green infrastructure and logistics that, on one side, promote economic growth. However, on the other side, it helps improve environmental quality, which ultimately improves the OBRI economies' health status.